A new species of Caulophacus (Hexactinellida: Lyssacinosida: Rossellidae) from the western Pacific Ocean, with new insights into the mitochondrial genome characteristics of hexactinellid sponges - Gong, Lin; Yang, Mei; Janussen, Dorte; Dohrmann, Martin; Li, Xinzheng (Frontiers in Marine Science, 2023)
A new species, belonging to the rossellid subfamily Lanuginellinae Gray, 1872, is described based on two specimens collected from two different seamounts in the western Pacific Ocean. Species characterization was approached by analyzing the morphological and skeletal features as well as the complete mitochondrial genome. Caulophacus (Caulodiscus) iocasicus sp. nov. is distinguishable from its congeners by its branched external shape and a unique combination of microscleres. It only has hemionychohexasters while other C. (Caulodiscus) species additionally have either onychohexasters or discohexasters. Furthermore, the new species has microhexactins, which have not been reported from the other six species of C. (Caulodiscus). Regarding the mitochondrial genome, the occurrence of the atp8 gene, the absence of tRNA E, the translocation of tRNA D between cob and nad6, and the rearrangement of nad6-nad4 distinguish the new species from other rossellids and even other hexactinellids for which mitogenomic information is available. The herein revised morphological and molecular information of the genus Caulophacus also suggests that the monospecific subgenus C. (Caulophacella) should be removed from Caulophacus and reinstated as a separate genus in the subfamily Lanuginellinae.